Moderatisme Islam Pesantren Dalam Menjawab Kehidupan Multikultural Bangsa - Mohamad Farid; Ahmad Syafi'i (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
Islamic pesantren or pesantren cottage can be termed as Aswaja Kiai which became an Islamic heritage of the wali have unique and extraordinary features in the history of Islamic da'wah in Indonesia known as moderate aswaja featuring Islamic features that are polite, peaceful, not pushy, not extreme right, no extreme left, by the scholars' or Kiai is very dominant coloring its role in the development of da'wah moderatisme system or learning through boarding school, as well as the development of the nature of religious rituals characterized by tasawwuf holiness that is not fatalistic let alone hedon matrial dried Aswaja teachings is very rooted and residing dihe along with the development of Islamic society of Indonesia a majmuk and multicultural. He seemed to be a form of moderate Islam that rahmatan lil alamin for the life of nation and community, so reasonable, if he to this day still exist and able to do self-actualization with the development of society. Keyword; moderatism, Islam, pesantren.